Toll like receptors: an overview - Shah, Gopi; Patel, Bharat; Chorawala, Mehul (International Journal of Pharmacology and Toxicology, 2014)
Toll like receptors (tlrs) are first identified in drosophila and recognise pathogen associated molecular patterns (pamps) expressed by various micro-organisms and are also known as pattern recognition receptors (prrs). pamps are important for both innate and adaptive response. Among all tlrs, tlr1, tlr2, tlr3 and tlr4 are expressed on plasma membrane while tlr3, tlr7, tlr8 and tlr9 are expressed intracellularly. Downstream signalling of tlr activation involves expression of numerous cytokines, chemokines and co-stimulatory molecules such as irak, traf, tirap and sarm via myd88 dependant and independent pathway. This is a key step for both innate and adaptive immunity. tlrs play an important role in pathogenesis of various diseases including infectious diseases, autoimmune diseases, neurodegenerative diseases, lung disease, skin disease and cancer. Most studied tlrs are tlr2, tlr4, tlr3 and tlr9. In brief, this review emphasizes on types of tlr, their ligands, location, signalling pathway and role in various diseases. Keywords: Toll like Receptors, Pathogen Molecular Patterns, Myd88 Pathway, Adaptor Proteins.